What happened to the transatlantic capital market relations? - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
This paper investigates the capital market relations between Euroland and the USA from 1990 until 2006. Formally based on the uncovered interest rate parity (UIP), backward recursive estimations establish a long-run equilibrium between European and US government bond yields. Since the mid-1990s though, cointegration can only be achieved additionally considering the exchange rate. The reason proves a stochastic trend common to the European interest and the exchange rate, consistently explained by central bank reactions and unfinished learning processes on the role of the euro. Furthermore, the US capital market dominance is strongly reduced, leading to transatlantic interdependence at eye level.
Keywords: E44; F31; C32; 330; Capital Market; UIP; Euro Area; United States; Internationaler Finanzmarkt; Zinsparität; Öffentliche Anleihe; EU-Staaten; USA